Asupan Energi dan Status Gizi Mahasiswa Saat Pandemi COVID-19 - Rambing, Chorinne J. E.; Bolang, Alexander S. L.; Kawengian, Shirley E. S.; Mayulu, Nelly (UNIVERSITAS SAM RATULANGI, 2021)
Abstract: The COVID-19 pandemic has caused major health problems as well as social and economic instability. Mitigation measures, such as quarantine, work from home, study from home, can affect the food supply chain and cause food and nutrition insecurity in various regions of the world. The research objective was to determine the relationship between energy intake and nutritional status of students at the Faculty of Medicine, University of Sam Ratulangi Manado during the COVID-19 pandemic. An observational analytic study was conducted with a cross-sectional approach which was conducted from September - December 2020 to 105 students who met the sample criteria. Energy intake data were obtained from a 2x24 hour food recall questionnaire with the google spreadsheet application and the survey survey. Nutritional status data based on BMI were obtained via e-questionare with the google form application. Correlation analysis was performed using the Spearman rank test in the SPSS program. The total energy intake of the respondents was 1583.07 ± 408.024 kcal. As many as 8 people had underweight nutritional status, 46 people had normal nutritional status, 20 people had At risk nutritional status, 26 people with obese 1 nutritional status and 5 people with obese 2 nutritional status as many as 5 people. There was no significant relationship (p ≥ 0.05) between energy intake and nutritional status.Keyword: COVID-19, energy intake, nutritional Status. Abstrak: Pandemi COVID-19 selain telah menyebabkan masalah kesehatan yang besar juga mengakibatkan ketidakstabilan sosial dan ekonomi. Upaya-upaya penanggulannya antar lain seperti karantina, work from home, study from home dapat mempengaruhi rantai pasokan makanan dan menimbulkan situasi ketidakamanan pangan dan gizi di berbagai wilayah di dunia. Tujuan penelitian untuk mengetahui hubungan antara asupan energi dan status gizi mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado saat Pandemi COVID-19. Penelitian analitik observasional dilakukan dengan pendekatan crossectional yang dilaksanakan dari bulan September - Desember 2020 pada 105 mahasiswa yang memenuhi kriteria sampel. Data asupan energi diperoleh dari kuesioner food recall 2x24 jam dengan aplikasi google spreadsheet dam mutrisurvey. Data status gizi berdasarkan IMT diperoleh melalui e-questionare dengan aplikasi google form. Analisis korelasi dilakukan dengan spearman rank test pada program SPSS. Asupan energi total responden yaitu 1583,07 ± 408,024 kkal. Sebanyak 8 orang memiliki status gizi underweight, sebanyak 46 orang status gizi normal, 20 orang status gizi At risk, status gizi obese 1 sebanyak 26 orang dan 5 orang status gizi obese 2 sebanyak 5 orang. Tidak ditemukan adanya hubungan yang bermakna (p ≥ 0,05) antara asupan energi dengan status gizi.Keyword : COVID-19, asupan energi, status gizi.